Algorithmic Trading Strategies: Automating and Back-testing the Perfect Order Strategy - Pereira, Otavio Silva (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management